Detection of the optimal analytical conditions for the determination of the copper ion using potentiometric titration (Latakia University Journal -Basic Sciences Series, 2018)
The objective of this study is to study some of the optimal analytical conditions for the determination of the Cu2+ ion using potentiometric titration method using the platinum electrode as a working electrode and the AgCL/Ag as a Reference electrode.In this study, the technical conditions were studied (working Electrode type, Reference Electrode type, Direction of titration, delay time, Proportional band, Speed of stirring)and the analytical conditions (pH value, time factor, quantity of solid KI added, electrolyte type and its concentration, detection limit) were studied using oxidation - reduction reactions as the method of iodide titration which applied successfully electrochemical for determine the Cu2+ ion.  The study showed that the typical Value of PH was (2.6 ± 0.1) and the time value before the titration was (5-7 min), the amount of potassium iodide was (0.4 g) and the study shows that the typical electrolyte was acetic acid and its concentration was (0.5-0.6 mol/l).The detection limit value of the Cu2+ion was (9.38×10-5mol/l) when the proposed conditions is applied.Some statistical coefficients like Recovery, standard deviation, Relative standard deviation show the accuracy and validity of the proposed method which were (98-101.56%)   (2.702×10-4 - 4.235×10-6), (2.265 - 4.170) respectively.The potentiometric method was applied to the new conditions on water samples and compared with the results measured in the optical spectrophotometric method, which showed good applicability with high reliability.